#TITLE_ALTERNATIVE# - (NIM : 101 08 074); Pembimbing : Dr. Djoko Suprijanto, ANTHONY
A group code over an abelian group G is a subset of Gn which forms a group under componentwise group operation. We will generalized matrix characterization of MDS (Maximum Distance Separable) linear codes over …nite …elds to MDS group codes over abelian groups, using quasideterminants de…ned for matrices over non-commutative rings.